The Role of the Principal in Optimizing Educational Management in Schools with Limited Resources - Abdul Jabar Albajili; Rozi Rozi; Elisa Safitri; Amaliyah Amaliyah; Tri Wahyuni (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the role of the principal in optimizing educational management in schools with limited resources through a case study of Bahrul Ulum Islamic Junior High School in South Tangerang. This school serves orphaned and underprivileged students, and therefore faces various limitations, particularly in funding, facilities and infrastructure, and the availability of teaching staff. This research used a qualitative approach with a case study method, with data collection conducted through interviews, observation, and documentation. The results indicate that the principal plays a strategic role in various aspects of educational management, including program planning oriented towards strengthening faith and piety (IMTAQ) and science and technology (IPTEK), adaptive human resource organization, optimizing the use of facilities and funding through collaboration, and implementing ongoing supervision and evaluation. These findings indicate that the principal's collaborative, humanistic, and socially oriented leadership is able to maintain and improve educational quality despite limited resources.